Microstructural modeling of the fragmentation of ordinary chondrites - Mostafa M. A. Mohamed; Mohamed H. Hamza; Laurence A. J. Garvie; Desireé Cotto-Figueroa; Erik Asphaug; Aditi Chattopadhyay (Scientific Reports)
Abstract The fracture behavior of rocks on asteroids offers insights into the evolution and dynamics of their boulders and regolith while providing critical data for developing hazard mitigation strategies. Information about the mechanical properties of asteroidal boulders primarily comes from laboratory studies of meteorites. This study examines the fracture mechanics of an ordinary chondrite (OC) using an innovative combination of experimental and computational methods to create models for the fragmentation processes of asteroidal materials. This approach illustrates how microstructural features—such as grain spacing and micropores—affect fracture behavior. Our results highlight the importance of microstructure in controlling fracture behavior, with normal stresses surpassing shear stresses in the primary minerals. Micropores accelerate fragmentation by facilitating the formation of multiple cracks. Olivine, plagioclase, and pyroxene demonstrate greater damage than troilite and kamacite, emphasizing differences in load-carrying capacity among these minerals. The findings offer insights for planetary science and the development of planetary defense strategies.